Early Cretaceous Slump Deposits in Laiyang Group (Lingshan Island, East China): New Constraints for Provenance Identification and Tectonic Evolution - Wang, Yuzhe; Qiu, Longwei; Yang, Yongqiang; Yang, Baoliang; Dong, Daotao; Khan, Danish; Guo, Zhongren (Frontiers in Earth Science, 2022)
The sedimentary strata in the Lingshan Island area are gaining attention because of their unique sedimentary and tectonic characteristics. However, the provenance, the depositional and tectonic setting in this area remain the focus of controversy. There is a significant slump deposit with lateral length up to 250 m in the Laohuzui section at the top of the Laiyang Group, which differs from the underlying turbidite deposits in morphology and composition. The sandstone in the Laohuzui section was continuously sampled and analyzed for major trace and rare earth elements. The results showed that the Laohuzui section is mixed with a continental margin provenance from the re-cyclic deposition in the arid region, which is different from the continental island arc provenance in the lower part of the Laiyang Group. Through the geochemical study of the igneous gravel contained in the olistolite and the comparison with the igneous rocks in the surrounding area, it is observed that the properties of the igneous gravel are most like those of the igneous rock deposit in the Zhucheng-Taolin area. In addition, the Lingshan Island and the Zhucheng-Taolin areas have similar sedimentary processes, suggesting that both received provenance from the Jiaonan uplift at the end of the Early Cretaceous. This study clarified the depositional processes of the later period of Laiyang Group deposition in the Lingshan Island area is expounded.